Role of spindle assembly checkpoint proteins in gametogenesis and embryogenesis - Pun, Renju; North, Brian J. (Frontiers in Cell and Developmental Biology, 2025)
The spindle assembly checkpoint (SAC) is a surveillance mechanism that prevents uneven segregation of sister chromatids between daughter cells during anaphase. This essential regulatory checkpoint prevents aneuploidy which can lead to various congenital defects observed in newborns. Many studies have been carried out to elucidate the role of proteins involved in the SAC as well as the function of the checkpoint during gametogenesis and embryogenesis. In this review, we discuss the role of SAC proteins in regulating both meiotic and mitotic cell division along with several factors that influence the SAC strength in various species. Finally, we outline the role of SAC proteins and the consequences of their absence or insufficiency on proper gametogenesis and embryogenesis in vivo.